2022
DOI: 10.3390/molecules27123853
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Quinazoline-2,4(1H,3H)-Dione Derivatives as Potential Antibacterial Agent: Design, Synthesis, and Their Antibacterial Activity

Abstract: In this paper, we report on the design and synthesis of a novel series of quinazoline-2,4(1H,3H)-dione derivatives as fluoroquinolone-like inhibitors of bacterial gyrase and DNA topoisomerase IV to identify and develop antimicrobial agents to prevent bacterial resistance problems. Their structures were confirmed using spectroscopic analyses (IR, NMR, and EI-MS). The novel quinazoline-2,4(1H,3H)-dione derivatives were evaluated for their antimicrobial activities against Gram-positive and Gram-negative bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…For this reason, the biological screening was expanded to evaluate the antimicrobial activity of alkenes 24a–d and diastereoisomeric mixtures of isoxazolidines ( cis - 20a / trans - 20a (10:90), cis - 20b / trans - 20b (8:92), cis - 20c / trans - 20c (6:94), cis - 20d / trans - 20d (10:90), cis - 21a / trans - 21a (10:90), cis - 21b / trans - 21b (15:85), cis - 21c / trans - 21c (10:90), and cis - 21d / trans - 21d (15:85)) towards selected bacterial strains ( E. faecalis ATCC 29212, S. aureus ATCC 2593, B. cereus PCM 1948, E. coli ATCC 25922, and P. aeruginosa ATCC 27853) and two fungal strains (C. albicans ATCC 10241 and A. brasiliensis ATCC 16404). Previous studies have shown that compounds containing a substituted quinazoline-2,4-dione moiety exhibit promising activity against Gram-negative and Gram-positive bacteria and fungi [ 9 , 23 , 24 , 25 ]. The antimicrobial activity was expressed as the MIC, minimal inhibitory concentrations, and the MBC, minimal bactericidal concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the biological screening was expanded to evaluate the antimicrobial activity of alkenes 24a–d and diastereoisomeric mixtures of isoxazolidines ( cis - 20a / trans - 20a (10:90), cis - 20b / trans - 20b (8:92), cis - 20c / trans - 20c (6:94), cis - 20d / trans - 20d (10:90), cis - 21a / trans - 21a (10:90), cis - 21b / trans - 21b (15:85), cis - 21c / trans - 21c (10:90), and cis - 21d / trans - 21d (15:85)) towards selected bacterial strains ( E. faecalis ATCC 29212, S. aureus ATCC 2593, B. cereus PCM 1948, E. coli ATCC 25922, and P. aeruginosa ATCC 27853) and two fungal strains (C. albicans ATCC 10241 and A. brasiliensis ATCC 16404). Previous studies have shown that compounds containing a substituted quinazoline-2,4-dione moiety exhibit promising activity against Gram-negative and Gram-positive bacteria and fungi [ 9 , 23 , 24 , 25 ]. The antimicrobial activity was expressed as the MIC, minimal inhibitory concentrations, and the MBC, minimal bactericidal concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, quinazoline-2,4-dione derivatives were recognized as inhibitors of several cancer-related enzymes [18] (including carbonic anhydrases IX and XII [19], histone deacetylase-6 [20], VEGFR-2 [21], tankyrases [22], aminopeptidase [23]) and as modulators of autoimmune processes [24][25][26][27]. Moreover, they are widely used to combat viral [28,29], bacterial [30][31][32], parasitic [33][34][35], and fungal [36] infections.…”
Section: Introductionmentioning
confidence: 99%